2011
DOI: 10.2136/sssaj2010.0124nps
|View full text |Cite
|
Sign up to set email alerts
|

Role of Natural Nanoparticles in Phosphorus Transport Processes in Ultisols

Abstract: Labile P is a well-recognized nonpoint sourec pollutant in agroecosystems. Predicting the fate and transport of P in watershed systems is critical in protecting water quality. In this case study, we investigated the role of soil nanoparticles in P release in South Carolina agricultural soils. Batch desorption experiments were coupled with scanning and transmission electron microscopy (EM) and x-ray absorption spectroscopy (XAS) to better assess the reactivity of soil nanoparticles. The surface soils contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…This shows that amorphous Fe/Al oxides are more important for P bonding compared to crystalline Fe/Al oxides. Several researchers have already reported that P was dominantly associated with amorphous Fe and Al oxides fractions in various soil types in the USA (Arai et al, 2005;Rick and Arai, 2011). It was presumed in those studies that specific anion adsorption (e.g., P) suppressed the transformation from amorphous to crystalline Fe oxides (Arai et al, 2005;Biber et al, 1994), which could Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that amorphous Fe/Al oxides are more important for P bonding compared to crystalline Fe/Al oxides. Several researchers have already reported that P was dominantly associated with amorphous Fe and Al oxides fractions in various soil types in the USA (Arai et al, 2005;Rick and Arai, 2011). It was presumed in those studies that specific anion adsorption (e.g., P) suppressed the transformation from amorphous to crystalline Fe oxides (Arai et al, 2005;Biber et al, 1994), which could Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…adsorption capacities and some studies showed amorphous Fe/Al oxides carried the majority of P in soils, despite higher abundance of crystalline Fe oxides (Arai and Livi, 2013;Arai et al, 2005;Rick and Arai, 2011). Few studies have distinguished organic and inorganic P associated with different Fe/Al oxides (i.e., amorphous and crystalline Fe/Al oxides) (Mahieu et al, 2000), despite the fact that P speciation will ultimately determine the different P bioavailability, mobility and mineralization in soil (Dick and Tabatabai, 1978;Liu et al, 2014).…”
Section: Jiang Et Al: Speciation and Distribution Of P Associatedmentioning
confidence: 99%
“…More importantly, XANES requires only minor amounts (milligram level) of samples for analysis; thus, it is an ideal tool to probe the speciation of P coll , especially considering the low yield of colloidal samples isolated from soils. To our knowledge, however, there has only been indirect use of Fe X-ray absorption spectroscopy on colloid-and nanoparticle-associated P transport (Rick and Arai, 2011); there has been no direct application of P-XANES to speciate P coll . Additionally, P-XANES provides only limited information about P o species (e.g., Kruse and Leinweber, 2008).…”
Section: Molecular Speciation Of Phosphorus Present In Readily Dispermentioning
confidence: 99%
“…They are typically formed by weathering processes, secondary mineral formation, or occur as degradation products in the form of organic colloids. Due to their surface charge and high specific surface area, nanoparticles and colloids exert a decisive control on the mobility and bioavailability of strongly adsorbing compounds such as P i and P o (Haygarth et al, 1997;Rick and Arai, 2011;Montalvo et al, 2015). The colloidal-sized main carriers for P in the acidic forest soils are in the first instance (hydr)oxides of Fe, Al, and Mn.…”
Section: Introductionmentioning
confidence: 99%
“…The binding of P, especially P o may further enhance the stability of colloidal suspensions of metal(hydr)oxides Ilg et al, 2009). Nanoparticles and colloids have been shown to act as important vectors of P transport in water and soils (Haygarth et al, 1997;Haygarth et al, 2006;Granger et al, 2007;Rick and Arai, 2011;Gottselig et al, 2014). They are known to contain > 50% of the total P in soil water samples (Hens and Merckx, 2001).…”
Section: Introductionmentioning
confidence: 99%